Sociodemographic Profile of Homeless in Serbia - Bobic, Mirjana Veljko (Sociološki pregled, 2020)
This is one of the rare papers on the homeless in Serbia, aimed to feature their sociodemographic profile. Main source of data is population census and the basic method is statistic. In addition,we apply secondary analysis of few qualitative researches, the findings of which were used as complementary. As a result, we present that vast majority of homeless are men, younger and middle aged, unmarried, with poor education and performing elementary occupations. Many of them are Roma and immigrants from the region and returnees from the EU as well. The interpretation of the findings, preempted by short overview of the social context of this phenomenon in Serbia and partly in EU, contributed to a conclusion which summarizes the profile of homeless and indicates onto an intervention targeted to pull them out of the social margin but also prevent further falls of many persons under risk.
Keywords: Homeless; Serbia; Socio-demographic profile; Social construction of the phenomenon; Social exclusion